Penerapan model pembelajaran missouri mathematics project untuk meningkatkan kemampuan pemecahan masalah matematika pada siswa kelas X SMA Negeri 1 Sipoholon - Olivia Nababan (Papanda Publisher, 2026)
This study aims to improve students’ mathematical problem-solving skills through the implementation of the Missouri Mathematics Project (MMP) learning model. The background to this study is based on students’ low ability to solve problem-solving questions, as evidenced by the fact that only 27% of students achieved the required standard in the initial test. This study is a classroom-action-research (CAR) comprising two cycles, each cycle involving planning, action, observation, and reflection. The research subjects were 30 Year 10 students at State Senior High School 1 Sipoholon. Data were collected through tests, observations, and interviews. The results showed an increase in the average problem-solving ability from 28.83 (29%) in the pre-test to 57.91 (58%) in Cycle I, and 85.5 (86%) in Cycle II, with N-Gain values of 0.396 (moderate) and 0.657 (high) respectively. In addition to cognitive improvements, the MMP also had a positive impact on students’ attitudes, such as discipline, self-confidence, independent learning, and active participation in discussions. This study demonstrates that the MMP learning model is effective in enhancing mathematical problem-solving skills whilst strengthening the quality of the mathematics learning process in the classroom